Complete mitochondrial genome sequence of E. suratensis revealed by next generation sequencing. Issue 1 (1st January 2016) - Mohanta, Sudip K.; Swain, Subrat K.; Das, Sofia P.; Bit, Amrita; Das, Gargee; Pradhan, Sanghamitra; Sundaray, Jitendra K.; Jayasankar, P.; Ninawe, A. S.; Das, Paramananda
Abstract: The complete mitochondrial genome of Etroplus suratensis, the Green chromide cichlid, was determined for the first time through NGS method. The genome is 16, 467 bp (Accession no. KU301747) in length and consisted of 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes and one control region. Organization of genes and their order are in accordance with other vertebrates. The overall base composition on plus strand was A: 28.3%, G: 15.2%, C: 30.9%, T: 25.6%, and the A + T content 53.9%. The control region contains a putative termination-associated sequence and three conserved sequence blocks. This mitogenome sequence data would play an important role in population genetics and phylogenetics of cichlid fish of India.